Returns from investing in U.S. equity mutual funds 1992 to 2011. - Chen, Si. (2013)
The purpose of this paper is to study survivorship bias and persistence of fund returns in equity mutual funds from 1992 to 2011. More specifically, we studied survivorship bias by comparing the returns of mutual funds that existed each year with those that survived till the end of the 20-year period. Our results show that there is substantial survivorship bias, with the biased returns averaging 0.11% higher than non-biased returns over the 20 years. In this case, excluding non-surviving funds will significantly overstate the returns received by mutual fund investors. Our findings show that there is higher performance persistence of mutual fund returns in the 1990s as compared to 2000s by about 3.5%. The high persistence of returns is used to simulate buying strategies for an investor so that he may be able to obtain returns that can outperform the market. The results of the first buying strategy of purchasing the top 10 to 40 funds are generally not in favour of the investor. On the other hand, the second strategy of purchasing the best 20 funds in the preceding 10-year period yields favourable results.